Membangun Jiwa Wirausaha Siswa Melalui Kegiatan Jual Beli (Analisis Kegiatan Market Day) - KMT Lasmiatun; Suci Novita Wijayanti; Yenti Afriani; Dodi Setiawan Riatmaja; Fadli Agus Triansyah; Imam Prawiranegara Gani (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of buying and selling activities, especially market-day activities, in building students' entrepreneurial spirit. Entrepreneurship plays an important role in preparing students to face the challenges of an increasingly complex and dynamic world of work. However, the development of entrepreneurial spirit is often not a major concern in formal education. Market Day activities in schools can be an effective means of building students' entrepreneurial spirit. This study uses a qualitative research method with a descriptive approach. Through interviews and data analysis, it was found that implementing market days in schools can develop students' entrepreneurship skills. Students are actively, creatively, and innovatively involved in carrying out tasks related to the Market Day. They learn to create new ideas, interact with customers, manage finances, and deal with various situations and conditions. The results showed that Market Day activities were effective in instilling entrepreneurial spirit and mental character in the students. Several important entrepreneurial characteristics such as creativity, self-confidence, adaptability, financial responsibility, effective communication, cooperation, and decision-making skills can be developed through buying and selling activities on the Market Day. By understanding the positive influence of buying and selling activities in building students' entrepreneurial spirit, this research provides a better understanding of the importance of including such activities in the education curriculum. The results of this research are expected to be the basis for developing educational strategies and policies that are more effective in preparing students to become successful entrepreneurs in the future.